Banks CSR-fit, customers' quality of life, and cross-buying: A joint moderation model - Ogunmokun, Oluwatobi A.; Timur, Seldjan; Bayighomog, Steven W.; Ikhide, Juliet E. (Wiley, 2021)
The purpose of the current study is first to investigate attitudinal loyalty as a mediator of the relationship between corporate social responsibility (CSR)-fit and cross-buying, before examining the interaction of CSR-fit, CSR support, and quality of life in predicting cross-buying through attitudinal loyalty. In total, 821 bank customers provided data for this study by filling online and in-person surveys. The results from data analysis reveal that customers' perceived CSR-fit relationship with cross-buying behavior is mediated by their attitudinal loyalty toward their bank. Moreover, the conditional process analysis indicated that while CSR support strengthened the relationship of CSR-fit and attitudinal loyalty, quality of life weakened this relationship. Specifically, in response to their banks' CSR-fit, respondents with high CSR support and perceived low quality of life were the most likely to be loyal and engage in cross-buying behaviors. The least, however, are those with low support and perceived high quality of life. This study enlightens our understanding of the intricate relationship between CSR-fit perceptions and loyalty attitudes and behaviors. It further proposes a complex model investigating the psychological contingencies of the relationship and its marketing implication in the financial sector.
Keywords: cross-buying; CSR-fit; CSR support; quality of life; retail bank industry